2017
DOI: 10.1186/s13104-017-3034-6
|View full text |Cite
|
Sign up to set email alerts
|

A predominance of hypertensive heart disease among patients with cardiac disease in Buea, a semi-urban setting, South West Region of Cameroon

Abstract: ObjectiveThe pattern of heart disease is diverse within and among world regions. The little data on the spectrum of heart disease in Cameroon has been so far limited to major cities. We sought to describe the pattern of heart disease in Buea, the South West Region of Cameroon, a semi-urban setting. This was a descriptive cross-sectional study. Between June 2016 and April 2017 the echocardiography register of the Buea Regional Hospital was surveyed. We extracted data on the age, sex and echocardiographic diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
(30 reference statements)
2
8
9
1
Order By: Relevance
“…More than half of reported cases were related to degenerative processes. Our findings are contrary to those of Jingi et al and Nkoke et al of the West and Southwest regions of Cameroon respectively, who reported cardiomyopathies as the second leading type of heart disease [9,10].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…More than half of reported cases were related to degenerative processes. Our findings are contrary to those of Jingi et al and Nkoke et al of the West and Southwest regions of Cameroon respectively, who reported cardiomyopathies as the second leading type of heart disease [9,10].…”
Section: Discussioncontrasting
confidence: 99%
“…Hypertensive heart disease was the leading type of heart disease in our setting, accounting for 41.1 %. This is similar to findings of Tchoumi and Bureta conducted in a rural setting of the Northwest Region [11] and other semi-urban and urban settings in Cameroon [9][10][11]17]. Given the high hypertension rates in the general Cameroonian population [18], coupled with the contrastingly poor awareness, treatment and control rates [16,[18][19][20], our findings were expected.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…878 titles and abstracts were screened; nine papers provided relevant information on etiologies of cardiac failure in SSA [20][21][22][23][24][25][26][27][28], nine additional papers were identified by reviewing references [18,[29][30][31][32][33][34][35][36].…”
Section: Epidemiology Of Heart Disease In Sub-saharan Africamentioning
confidence: 99%